IDENTIFICATION OF BOOK LABELING DESIGN IN LIBRARY USING RADIO FREQUENCY IDENTIFICATION (RFID) SYSTEM - Agung Rachmatullah; Arif Faizin (Sean Institute, 2023)
The library, as an essential institution in education and knowledge, continually seeks innovation to enhance operational efficiency and visitor services. One technology that has garnered attention is Radio Frequency Identification (RFID). This research aims to identify the optimal design for book labeling in libraries by leveraging RFID systems. This technology offers a potential automation solution for processes like borrowing, returning, and inventory management of books. The implementation of RFID in libraries can yield significant benefits. Key advantages include increased efficiency in serving borrowers, reduced human errors in data recording, and the ability to gather accurate data for book collection analysis and borrowing trends. However, the implementation of RFID also involves several challenges, including initial implementation costs, integration with existing infrastructure, as well as privacy and data security aspects. Additionally, the reading range of the RFID RC522 sensor is limited to 10 cm, which can be reduced to 1 cm to 6 cm if obstructed by objects, and if obstructed by solid objects like metal, it might not be read even at a 1 cm distance due to thickness. A solution that can be employed is using a plastic cover for the sensor with a thickness that is not excessively high.